Jesus and Ubuntu exploring the social impact of Christianity in Africa - Ntarangwi, Mwenda 1964- (Trenton, NJ [u.a.] Africa World Press, 2011)
Introduction : African Christianity : Africa, politics, and socioeconomc realities / Mwenda Ntarangwi -- Faith and politics in post-colonial Africa / David Hoekema -- Culture, missions, and Africa's lessons for Western Christianity / Caitlin McGill -- Charismatic renewal in the Catholic Church in Ghana / Ross Acheson -- Charismatic renewal : lessons in missions from the Kenyan church / Joshua S. Kuipers -- The Gospel for Ethiopia by Ethiopians : Mapping the contested terrains between Pentecostals and Marxist Radicals / Tibebe Eshete -- From the fringes to the centre : Pentecostal Christianity in the public sphere in Kenya (1970-2009) / Damaris S. Parsitau -- The Catholic Church and civic education in the slums of Nairobi / Christine M. Bodewes -- Reflecting on church-state relationship in Kenya / Njonjo Mue -- Literacy teaching and learning in Sierra Leone / Johanna Kuyvenhoven
Literacy teaching and learning in Sierra Leone Johanna Kuyvenhoven.
"Essays in this volume come out of a conference on the social impact of Christianity in Africa held at the campus of Calvin College in the summer of 2009"--Introd. - Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Christian Sociology -- Congresses -- Africa, Sub-Saharan; Christian Sociology -- Africa, Sub-Saharan -- Congresses; Africa, Sub-Saharan -- Congresses -- Church history; Africa, Sub-Saharan -- Church history -- Congresses; Konferenzschrift